Grindagutar på sjukeheim: Tilsette sin erfaring med kulturprosjekt - Fossøy, Aud Berit; Hauge, Solveig; Grov, Ellen Karine (Nordisk Tidsskrift for Helseforskning, 2014)
Grindagutar at nursing home: Employees experience with cultural project.Background: Culture activity contributes to holistic care for nursing home residents, and the employees are key personnel for success.Aim: Explore the employees’ experience putting culture projects into life in a nursing home.Methods: The material, based on four focus group interviews with employees in the nursing home, is categorized and analyzed through text condensation.Results: The culture projects created activity and were sources for thriving. However, not participating directly in the activity, the employees let the artists in, were available for them, and watched the patients during the performances. Their function as “door-openers/-keepers” resulted in hosting responsibility, leading to a position of confusion regarding the role as protectors for the patients. Main challenges were how to give feedback regarding whether the patients liked/disliked the performance, and the feeling of being trapped in a position as bystander rather than making the culture activity a common happening for the patients and the employees.